Minimasi Cacat Produk Lightning Arrester di PT.XYZ dengan Pendekatan PDCA - Surani, Surani; Hima, Siti Muhimatul Khoiroh (Fakultas Teknik UMRI, 2025)
PT.XYZ is a manufacturing company specializing in high-voltage electrical insulators, including Lightning Arresters. The company faces a major quality issue, with a product defect rate of 4.6%, exceeding its maximum tolerance limit of 2%. This study aims to reduce the defect rate through a structured and continuous improvement approach using the PDCA (Plan-Do-Check-Act) cycle. Data were collected through field observations, interviews with relevant personnel, and analysis of historical production records. Findings reveal that the most prevalent defect originates from the injection process, specifically related to undercured material. The implementation of PDCA, supported by fishbone diagram and 5W+1H analysis, successfully formulated effective corrective actions. Post-implementation results indicate a significant decrease in defect rates. Consequently, this approach contributes to enhanced product quality, improved operational efficiency, and greater customer satisfaction.